Verification Of The Vibrational Theoretical Assignment Of The DADP Using Isotopic Labelling (2018)
This work deals with the comparison of the theoretical assignment of the DADP vibrational spectrum with the experimental displacements by isotopic labeling. For this, the DADP-C4 and DADP-C2 isotopomers were synthesized from acetone labeled isotopically in the methyl and the carbonyl carbon atoms, respectively. The acetone and DADP-isotopomer compounds were characterized using Raman and infrared spectroscopy. Theoretical assignments were taken from previous studies on the potential energy distribution of a vibrational mode, which provide an approach to the internal coordinates related to each band. The selective isotopic labeling allowed us to approach to the dependence of each band, because the energy of a molecular vibration also depends on the reciprocal mass of the atoms involved. In general, the results showed that some bands assigned experimentally do not coincide with the theoretical assignments by quantum mechanical simulations.